Aspectos toxicológicos de paration metílico e de extrato aquoso de folhas secas de nim (Azadirachta indica) para o pacu (Piaractus mesopotamicus) e eficácia no controle de monogenea Dactylogyridae - Cruz, Claudinei da [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
The objectives of the present study were 1) to determine the 50% lethal concentration (LC (l)50-96h) of methyl parathion and azadirachtin present in the aqueous extract of dry neem leaves (AEDNL) for pacu (Piaractus mesopotamicus), 2) to evaluate the efficacy, safe concentrations and exposure time of methyl parathion and azadirachtin for the control of Anacanthorus penilabiatus, 3) to assess the alterations that occur in the gills and liver of fish exposed to sublethal concentrations of methyl parathion and azadirachtin, and 4) to determine the presence of azadirachtin residues in pacu (Piaractus mesopotamicus) by high-performance liquid chromatography HPLC. The calculated LC (l) 50-96h of methyl parathion was 3.97 mg/L for fry pacu and 9.89 mg/L for juvenile fish. The LC (l) 50-96h of azadirachtin present in AEDNL was 1.20 and 1.18 mg/L for fry and juvenile fish, respectively. Methyl parathion was less toxic to fry and juvenile pacu than azadirachtin. In gills, methyl parathion caused congestion, lamellar fusion, subepithelial edema, interstitial hemorrhage, and disorganization of the lamellar structure, whereas azadirachtin caused subepithelial edema and apical fusion of secondary lamellae. In the liver, methyl parathion caused congestion, cell fusion, hepatocyte hyperplasia and derangement of the cord-like organization of hepatocytes, and azadirachtin caused disorganization of the cord-like arrangement of hepatocytes, cytoplasmic vacuolization, and necrosis of epithelial cells lining the bile canaliculi. Methyl parathion was more effective than the AEDNL in the control of monogenetic parasites, with this control being proportional to the increase of the insecticide's concentration in water and of exposure time. The highest efficacy of methyl parathion was observed at a concentration of 7 mg/L, with a 96.2% rate of parasite control after 16 h of exposure and a 97.0% rate after 24 h. For AEDNL, a...

Os objetivos desse trabalho foram determinar a concentração letal 50% (CL (I) 50-96h) do paration metílico e da azadiractina contida no extrato aquoso de folhas secas de nim (EAFSN) para o pacu (Piaractus mesopotamicus); avaliar a eficácia, concentrações seguras e o tempo de exposição do paration metílico e da azadiractina contida no EAFSN para o controle do Anacanthorus penilabiatus; avaliar as alterações nas brânquias e no fígado dos peixes expostos a concentrações subletais de paration metílico e a azadiractina; e determinar a presença resíduo de azadiractina por cromatografia líquida de alta eficiência (CLAE), no pacu (Piaractus mesopotamicus. A CL (I) 50-96h calculada do paration metílico foi de 3,97 mg/L para os alevinos e de 9,89 mg/L para os jovens. Para a azadiractina contida no EAFSN foi de 1,20 mg/L para os alevinos e de 1,18 mg/L para os jovens. O paration metílico foi menos tóxico para os alevinos e jovens de pacu do que a azadiractina. Nas brânquias, o paration metílico causou congestão, fusão lamelar, edemas subepiteliais, hemorragias intersticiais, fusão lamelar e desorganização da estrutura lamelar e a azadiractina, edema subepitelial, fusão apical das lamelas secundárias. No fígado, o paration metílico causou congestão, fusão celular, hiperplasia dos hepatócitos e desarranjo da organização cordonal dos hepatócitos e a azadiractina, desorganização do arranjo cordonal dos hepatócitos, vacuolização citoplasmática, necrose das células epiteliais de revestimento dos canalículos biliares. O paration metílico foi mais eficiente que o EAFSN no controle dos parasitos monogenéticos, cujo controle foi proporcional ao aumento da concentração na água e ao tempo de exposição. A maior eficácia do paration metílico foi com 7 mg/L, que controlou 96,2 % dos parasitos às 16 horas de exposição e 97,0% às 24 e do EAFNS, com 2,9 mg/L de...
Keywords: Peixe; Toxicologia; Pacu (Peixe); Produtos químicos agrícolas; Inseticidas; Fishes